INNOVATION IN LEARNING ARABIC WRITING SKILLS BASED ON ARTIFICAL INTELLIGENCE: QALAM.AI - Hidayah, Nurmalia; Muhamad, Sahrul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Writing is the highest skill for Arabic learners. To achieve the desired results, it requires Arabic writing skills learning innovation. For example, by utilizing the development of artificial intelligence technology to correct the grammar of Arabic texts. This study aims to determine the use of qalam.ai applications in correcting Arabic writing and user responses. The type of research used is qualitative with descriptive methods. Data collection was conducted through observation of the use of qalam ai, review of related documents, and interviews with four informants. Data analysis techniques in this study use the Miles and Huberman Model, namely data reduction, data presentation, and conclusions. The results of this study show that the Qalam application is a new innovation in learning maharah kitabah. Qalam has interesting features that can help users correct Arabic writing so that it becomes free from writing errors both in terms of imla', qawa'id, and punctuation. Therefore, users give a positive response to the qalam application and hope that this application continues to innovate and develop in order to detect Arabic writing errors more optimally.